Screening for Salinity Tolerance in Lowland Rice - Suhaimi Sulaiman (Zuriat, 1991)
Screening for breeding materials for salinity tolerance is most accurately done by measuring grain yields. However, mass screening during the vegetative period of plant development using pots in a greenhouse is more effective for rapid evaluation of large amounts of germplasm.In this study, Pokkall and IR 22 cultivars were grown in pots which contained five kilograms of soil. The soil had been fertilized with four liters of Hoagland's solution which was salinized with a given concentration of 0, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, and 6000 ppm NaCl. Four of two weeks old seedlings were transplanted into each pot. The experiment unit were arranged in a Randomized Complete Block Design (RCBD) with two replications.A salinity level of 4000 ppm NaCl (8.5 mmhos/cm EC) showed the best differentiation of phenotypic performance for the salinity tolerance evaluation four weeks after transplanting.This technique was also used for screening of 23 traditional cultivars from South Kalimantan at salinity level of 8.5 mmhos/cm EC. Pokkal was used as tolerant check, and IR 22 was use as a susceptible check.Bayar Putih, Pandak, Pucuk, Lemo, and Duyung cultivars were identified as the most tolerant cultivars. It was also found that the percentage of sodium was greater in susceptible plants than in tolerant ones. However, the differences in N, P, and K were relatively small.